Caracterização estrutural da porção central da Bacia de Santos e seu embasamento continental adjacente, através de interpretação de imagens de satélites e geofísicas - Lúcio, Thiago Domingues Góes [UNESP] (2011)
The Santos Basin is located in the Brazilian continental margin and includes the coast of Santa Catarina, Paraná, São Paulo and Rio de Janeiro states. Its northern limit is the Campos Basin through the High of Cabo Frio and the southern one with the Pelotas Basin through the Platform of Florianópolis, totaling an area of approximately 350,000 square kilometers in a water depth of 3,000 m. The Paranapanema Lineament has WNW / ESE direction, and extends from the area filled by the Paraná Basin, on the border between the states of Sao Paulo and Parana, lasting up to near the ocean floor along with the fracture zone of Rio de Janeiro. The Capricorn Lineament is a feature inherited from the separation between the continents of Africa and South America, and is the main structural feature NW / SE of the Santos Basin center-south region. These two structures together with other ones with continental origin may be associated with structural features in the sediments from the Santos Basin. This work aims to characterize the structures operating in the central portion of the Santos Basin based on subsurface data in the offshore area (2D seismic) together with data from the surface of the continental basement in a way to correlate the Santos Basin structures with the continental regional traits. This data interpolation showed that the structural features of the continent operates on the submerged zone, the seismic sections show these structural trends for the Paranapanema Lineament / Fracture Zone of Rio de Janeiro, Capricorn Lineament and two fault zones that exhibit structures typical of a transfer zone